Preparation, characterization and antioxidant activity of protocatechuic acid grafted carboxymethyl chitosan and its hydrogel. (15th January 2021) - Xu, Chao; Guan, Shui; Xu, Jianqiang; Gong, Weitao; Liu, Tianqing; Ma, Xuehu; Sun, Changkai
Highlights: PCA-g-CMCS conjugates were synthesized for oxidation-resistant material. The pH sensitivity of conjugates was preserved compared to raw CMCS. The sustained release of PCA from the biodegradable hydrogel could be achieved in vitro . The PCA-g-CMCS hydrogel attenuated H2 O2 -induced oxidative damage of SH-SY5Y cells. Abstract: In this study, protocatechuic acid (PCA) was grafted onto carboxymethyl chitosan (CMCS) via EDC/NHS to improve the antioxidant effect. The grafting ratio of PCA-g-CMCS conjugates could be controlled by adjusting the pH value and feed ratio of raw materials. The conjugates exhibited similar pH sensitivity to CMCS and showed dramatic enhancements of DPPH and ABTS radicals scavenging activities, total antioxidant capacity, reducing power, and Fe 2+ -chelating activity. Three-dimensional porous PCA-g-CMCS hydrogel was prepared by lyophilization and secondary cross-linking. The shaped hydrogel preserved its antioxidant activity, and the sustained release of PCA-containing degraded fragment from biodegradable hydrogel could be achieved with the aid of lysozyme in vitro (15 days). PCA-g-CMCS hydrogel also showed excellent biocompatibility and protective effect on H2 O2 -induced oxidative damage in SH-SY5Y cells. These results suggested that PCA-g-CMCS conjugates and its hydrogel would appear to be a promising oxidation-resistant material for applications such as drug release and tissue engineering.